BCI move: exploring pediatric BCI-controlled power mobility - Hammond, Leah; Rowley, Danette; Tuck, Corinne; Floreani, Erica Danielle; Wieler, Amy; Kim, Vella Shin-Hyung; Bahari, Hosein; Andersen, John; Kirton, Adam; Kinney-Lang, Eli (Frontiers in Human Neuroscience, 2025)
IntroductionChildren and young people (CYP) with severe physical disabilities often experience barriers to independent mobility, placing them at risk for developmental impairments and restricting their independence and participation. Pilot work suggests that brain-computer interface (BCIs) could enable powered mobility control for children with motor disabilities. We explored how severely disabled CYP could use BCI to achieve individualized, functional power mobility goals and acquire power mobility skills. We also explored the practicality of pediatric BCI-enabled power mobility.MethodsNine CYP aged 7-17 years with severe physical disabilities and their caregivers participated in up to 12 BCI-enabled power mobility training sessions focused on a personalized power mobility goal. Goal achievement was assessed using the Canadian Occupational Performance Measure (COPM) and Goal Attainment Scaling (GAS). The Assessment for Learning Powered Mobility (ALP) was used to measure session-by-session power mobility skill acquisition. BCI set-up and calibration metrics, perceived workload, and participant engagement were also reported.ResultsSignificant improvements in COPM performance (Z = −2.869, adjusted p = 0.012) and satisfaction scores (Z = −2.809, adjusted p = 0.015) and GAS T scores (Z = −2.805, p = 0.005) were observed following the intervention. ALP scores displayed a small but significant increase over time (R2 = 0.07–0.19; adjusted p = <0.001–0.039), with 7/9 participants achieving increased overall ALP scores following the intervention. Setup and calibration times were practical although calibration consistency was highly variable. Participants reported moderate workload with no significant change over time (R2 = 0.00–0.13; adjusted p = 0.006–1.000), although there was a trend towards increased frustration over time(R2 = 0.13; adjusted p = 0.006).DiscussionParticipants were highly engaged throughout the intervention. BCI-enabled power mobility appears to help CYP with severe physical disabilities achieve personalized power mobility goals and acquire power mobility skills. BCI-enabled power mobility training also appears to be practical, but BCI performance optimization and skill acquisition may be needed to translate this technology into clinical use.